Design and management of energy-efficient hybrid electrical energy storage systems - Kim, Younghyun (Springer International Publishing, 2014)
This book covers system-level design optimization and implementation of hybrid energy storage systems. The author introduces various techniques to improve the performance of hybrid energy storage systems, in the context of design optimization and automation. Various energy storage techniques are discussed, each with its own advantages and drawbacks, offering viable, hybrid approaches to building a high performance, low cost energy storage system.  Novel design optimization techniques and energy-efficient operation schemes are introduced. The author also describes the technical details of an actual prototype implementation of a 300 W scale hybrid energy storage system. ·         Provides system-level design optimization schemes to improve efficiency in hybrid energy storage systems; ·         Discusses system architectures and optimization techniques; ·         Includes technical details for implementing a physical prototype of a hybrid energy storage system.